Upaya Peningkatan Penjualan pada Rumah Makan Khas Jawa “TUGIAH” Melalui Digital Marketing - Safaruddin; Fitri, Nursiah; Siregar, Efni; Novita, Vivianti (Politeknik Negeri Medan, 2024)
The target audience of this Community Service Program (PKM) is an economically productive community, namely the typical Javanese restaurant “Tugiah” on Jalan K.L. Yos Sudarso, Km 7, Tanjung Mulia Village, Medan City. Tanjung Mulia, Medan City, North Sumatra Province. The partner's problem is the low sales turnover of partners per day; partners do not understand how to promote through social media, never prepare financial reports, and the physical condition of business equipment, such as tables and brand boards, is too worn out. physical condition of business equipment such as tables and signboards are too worn out. The solution offered is in the form of digital marketing training, which includes training in preparing financial reports and providing business equipment. The results of the implementation of the activity show that this service activity can overcome the problem of low business turnover with an increase in sales after marketing through the promotion of digital marketing activities. marketing through the promotion of digital marketing activities. The constraints and limitations of cooking utensils can be overcome by receiving a grant from the service implementers. The stall's unattractive appearance can be overcome by organizing or preparing banner stickers and business brand boards. Constraints ability to manage business finances, the PKM Team provided brief training on how to compile a cash book, Sales book, purchase Book, and business cost book.